Land Cover Changes Monitoring of Kerumutan Protected Forest by Using Landsat Imageris - Supriyan Syahrizal; Yossi Oktorini; Rudianda Sulaeman (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2018)
Kerumutan Protected Forest is a conservation forest area in Riau Province which has the characteristics of peat swamp forest. This area has a disturbance of forest areas, illegal logging and forest fires that affect changes in forest cover. To determine the land cover changes in Kerumutan Protected Forest, monitoring was conducted to see land cover changes in the area. The purpose of this research was determined the land cover changes condition in Kerumutan Protected Forest area through interpretation of landsat imageris during 1996, 2008, 2013, and 2017. This research was carried out using the overlay process, test of accuracy and classification of reports between two classes of land cover in different years so that changes could determined. Based on results from landsat imageris analysis during 1996, 2008, 2013, and 2017, the land cover area of Kerumutan Protected Forest has changed, during 1996-2018 the primary land cover of wetland forest decreased to 14164,56 ha, secondary wetland forest increased to 13392,81 ha, swamps land increased to 7,83 ha, shrubs land decreased to 251,55 ha, open ground land increased to 33,21 ha, water body decreased to299,7 ha. During 2008-2013 the primary wetland forest decreased to 5604,39 ha, secondary wetland forest decreased to 12378,06 ha, swamps land increased to 19016,64 ha, shrubs land increased to 482,67 ha, open ground land increased to 276,39 ha, body water increased to 318,8 ha. During 2013-2017 the primary wetland forest increased to 17527,23 ha, secondary wetland forest decreased to 16779,33 ha, swamps land decreased to 4298,49 ha, shrubs land increased to 81,36 ha, open ground land decreased to 880,83 ha, and the body water increased to 336,06 ha.